PENERAPAN PENDIDIKAN KARAKTER MELALUI BUDAYA SEKOLAH - AGUS WAHDIAN; Framz Hardiansyah (Universitas Islam Madura, 2021)
The development of the potential of students can be done through character education. A good school culture instills character values ​​in students. The aim is to find out the implementation of discipline character education, love for the homeland, and care for the environment through school culture which includes routine activities, spontaneous activities, exemplary, and conditioning at SDN Baban 1 Sumenep. Character education through school culture is education to shape personality through the atmosphere of school life where students interact which teaches ethical values ​​to shape personality which is manifested in one's real actions, namely good behavior, honesty, responsibility, respecting the rights of others, working hard, and so on. This study uses a qualitative approach with a descriptive qualitative form. The data needed in this research is data about the implementation of discipline character education, love for the homeland, and caring for the environment through school culture in the form of routine activities, spontaneous activities, exemplary, and conditioning at SDN Baban 1 Sumenep. The results obtained are the implementation of disciplined character education, love for the homeland, and care for the environment through school culture which includes routine activities, spontaneous activities, exemplary, and good conditioning at SDN Baban 1 Sumenep. Keywords: Character Education, Environmental Care, School Culture. Abstrak: Pengembangan potensi peserta didik dapat dilakukan melalui pendidikan karakter. Budaya sekolah yang baik menanamkan nilai-nilai karakter pada peserta didik. Tujuannya adalah untuk mengetahui pelaksanaan pendidikan karakter disiplin, cinta tanah air, dan peduli lingkungan melalui budaya sekolah yang meliputi kegiatan rutin, kegiatan spontan, keteladanan, dan pengkondisian di SDN Baban 1 Sumenep. Pendidikan karakter melalui budaya sekolah adalah pendidikan untuk membentuk kepribadian melalui suasana kehidupan sekolah tempat peserta didik berinteraksi yang mengajarkan nilai-nilai etika untuk membentuk kepribadian yang terwujud dalam tindakan nyata seseorang yaitu tingkah laku yang baik, jujur, bertanggung jawab, menghormati hak orang lain, kerja keras, dan sebagainya. Penelitian ini menggunakan pendekatan kualitatif dengan bentuk kualitatif deskriptif. Data yang yang diperlukan dalam penelitian ini adalah data tentang pelaksanaan pendidikan karakter disiplin, cinta tanah air, dan peduli lingkungan melalui budaya sekolah yaitu berupa kegiatan rutin, kegiatan spontan, keteladanan, dan pengkondisian di SDN Baban 1 Sumenep. Hasil penelitian yang diperoleh adalah pelaksanaan pendidikan karakter disiplin, cinta tanah air, dan peduli lingkungan melalui budaya sekolah yang meliputi kegiatan rutin, kegiatan spontan, keteladanan, dan pengkondisian di SDN Baban 1 Sumenep baik